Short- and medium-chain chlorinated paraffins in aquatic organisms from an e-waste site: Biomagnification and maternal transfer - Guan, Ke-Lan; Liu, Yu; Luo, Xiao-Jun; Zeng, Yan-Hong; Mai, Bi-Xian (The Science of the total environment, 2020)
[Display omitted] •Occurrence and congener profiles of S/MCCP were studied in organisms from a pond.•BMF was >1 in fish-watersnke food chain but was <1 in fish-waterbird egg chain.•Positive linear relationship between BMFs and number of Cl atom was observed.•Maternal transfer concentration ratios of S/MCCP were lower than 1 in watersnake.•Negative relationships were found between maternal transfer efficiencies and log KOW. Chlorinated paraffins (CPs) are globally pervasive contaminants that are toxic to humans and wildlife. Inconsistent biomagnification behaviors in different food chains have been reported, and very few studies have been conducted to investigate the maternal transfer of CPs in ovoviviparous species. This study investigated the biomagnification of short- and medium-chain chlorinated paraffins (S/MCCPs) in two aquatic food chains, as well as maternal transfer of S/MCCPs in watersnakes collected from an e-waste polluted pond in southern China. The concentrations of SCCPs and MCCPs varied from 1.2 to 250 μg/g lipid weight (lw) and from 2.3 to 200 μg/g lw in the collected organisms. The SCCP homologue profiles in prey (fish and prawn) differed from those in predators (watersnake and waterbird egg), while MCCP homologue group patterns were homogeneous. All maternal transfer concentration ratios (egg to muscle) of S/MCCPs in the watersnakes were lower than 1 and negatively correlated with the octanol–water partition coefficients (log KOW), different from the maternal transfer of halogenated aromatic pollutants in the watersnake. Biomagnification factors (BMFs) of S/MCCPs for fish–watersnake muscle food chain were larger than 1, while BMFs for the fish–waterbird egg food chain were less than 1. However, when watersnake egg was used to calculate BMF, no biomagnification was found. BMFs in the two food chains showed significant positive linear correlations with chlorine atoms, but no significant correlation with carbon atom numbers, which suggested that a congener-group-specific elimination and excretion process for S/MCCPs exist.